"Right tool, " wrong "job": Manual vacuum aspiration, post-abortion care and transnational population politics in Senegal. (June 2015) - Suh, Siri
Abstract: The "rightness" of a technology for completing a particular task is negotiated by medical professionals, patients, state institutions, manufacturing companies, and non-governmental organizations. This paper shows how certain technologies may challenge the meaning of the "job" they are designed to accomplish. Manual vacuum aspiration (MVA) is a syringe device for uterine evacuation that can be used to treat complications of incomplete abortion, known as post-abortion care (PAC), or to terminate pregnancy. I explore how negotiations over the rightness of MVA as well as PAC unfold at the intersection of national and global reproductive politics during the daily treatment of abortion complications at three hospitals in Senegal, where PAC is permitted but induced abortion is legally prohibited. Although state health authorities have championed MVA as the "preferred" PAC technology, the primary donor for PAC, the United States Agency for International Development, does not support the purchase of abortifacient technologies. I conducted an ethnography of Senegal's PAC program between 2010 and 2011. Data collection methods included interviews with 49 health professionals, observation of PAC treatment and review of abortion records at three hospitals, and a review of transnational literature on MVA and PAC. While MVA was the most frequently employed form of uterine evacuation in hospitals, concerns about off-label MVA practices contributed to the persistence of less effective methods such as dilation and curettage (D&C) and digital curettage. Anxieties about MVA's capacity to induce abortion have constrained its integration into routine obstetric care. This capacity also raises questions about what the "job, " PAC, represents in Senegalese hospitals. The prioritization of MVA's security over women's access to the preferred technology reinforces gendered inequalities in health care. Highlights: Explores manual vacuum aspiration practices and policies in a global South context. Shows influence of local and global abortion politics on MVA practices in Senegal. Shows how MVA's dual capacity challenges the meaning of PAC in Senegalese hospitals. Illustrates how MVA policies lead to persistence of less effective PAC treatment. Shows how prioritization of MVA security reinforces gendered health inequalities.